Ethnic Identity as a Mediator Between Cultural Involvement and Life Satisfaction: A Cross-Sectional Study of Andean Indigenous Adults - Andrés Gutiérrez-Carmona; Rodrigo-Alejandro Ardiles-Irarrázabal; Miguel Valencia-Contrera; Diego Henríquez; Alfonso Urzua (Journal of Transcultural Nursing, 2026)
Introduction: Acculturation processes threaten Indigenous well-being and cultural continuity. Guided by Leininger’s transcultural nursing theory, this study examined whether ethnic identity mediates the relationship between cultural involvement and life satisfaction among Lickanantay adults in northern Chile. Methods: A cross-sectional correlational design was used with 320 Lickanantay adults (56.3% women; Mage = 40.8). Participants completed validated measures of life satisfaction, cultural involvement, and ethnic identity. Structural equation modeling using weighted least squares maximum likelihood (WLSMV) estimation tested direct and mediational effects, controlling for age and gender. Results: Cultural involvement was positively associated with life satisfaction (β = .35, p < .001). Ethnic identity fully mediated this relationship (indirect effect β = .28, p < .001), and the direct effect became nonsignificant in the mediation model. Discussion: Ethnic identity is a key mechanism linking cultural practices to well-being. Findings support integrating ethnic identity into culturally congruent nursing care to promote Indigenous health equity.